Association Between The Implementation Of the Four Pillars Of Balanced Nutrition and Type 2 Diabetes Mellitus Among Elderly: A Case–Control Study - Nur Arfatunnisah; Nur Husnul Khatimah; Darmin Darmin; Juraidin Juraidin (MESINA (Medical Scientific Journal), 2026)
Type 2 Diabetes Mellitus (DM) is a non-communicable disease that has become a public health problem because its incidence continues to increase, especially among the elderly. One of the efforts to prevent and control this disease is the implementation of the four pillars of balanced nutrition, namely consuming a diverse diet, engaging in physical activity, practicing clean and healthy living behavior (CHLB), and monitoring body weight. This study aimed to determine the effect of implementing the four pillars of balanced nutrition on the incidence of Type 2 Diabetes Mellitus among the elderly in the working area of Penanae Public Health Center. This study used a quantitative method with a case-control design. The population consisted of 142 individuals, with a sample of 104 respondents comprising 52 respondents with Type 2 Diabetes Mellitus and 52 respondents without Type 2 Diabetes Mellitus selected using purposive sampling. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed a significant association between dietary diversity and Type 2 DM (p=0.000), physical activity (p=0.001), CHLB (p=0.000), and body weight monitoring (p=0.002). In conclusion, the four pillars of balanced nutrition influence the incidence of Type 2 Diabetes Mellitus among the elderly in the working area of Penanae Public Health Center. It is recommended that health education and promotion programs be strengthened to increase public awareness, particularly among the elderly, in adopting healthy lifestyles consistently as an effort to prevent and control Type 2 Diabetes Mellitus.Keywords: Type 2 Diabetes Mellitus, Elderly, Four Pillars of Balanced Nutrition,Diverse Diet, Physical Activity, Clean and Healthy Living Behaviors, Body Weight Monitoring.